ANALISIS PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SEKTOR CONSUMER NON CYCLICALS - Suharti, Suharti; Ilynn, Ilynn; Yani, Fitri; Putri, Novita Yulia; Suryani, Febdwi; Yusrizal, Yusrizal (Bilancia : Jurnal Ilmiah Akuntansi, 2023)
ABSTRACT This research aims to analyze the effect of the Current Ratio, Debt To Equity Ratio, Return On Assets, and Total Assets Turnover variables on the Profit Growth. The population in this research were all consumer non cyclicals companies listed on the Indonesia Stock Exchange. While the samples taken in this research were 43 companies using purposive sampling method. Secondary data were obtained from the IDX. The independent variables used are Current Ratio, Debt To Equity Ratio, Return On Assets, and Total Assets Turnover. The dependent variable used is Profit Growth. The data analysis technique used is Multiple Linear Analysis using the Smart PLS program. The results of this research indicate that the Current Ratio, Debt To Equity Ratio, Return On Assets have a positif and insignificant effect on the Profit Growth. While Total Assets Turnover variable has a negative and insignificant effect on the Profit Growth. Keywords: Consumer Non Cyclicals; Current Ratio; Debt To Equity Ratio; Return On Assets; Total Assets Turnover; Profit Growth. ABSTRAK Penelitian ini bertujuan untuk menganalisis pengaruh variabel Current Ratio, Debt To Equity Ratio, Return On Assets, dan Total Assets Turnover terhadap pertumbuhan laba. Populasi dalam penelitian ini adalah seluruh perusahaan consumer non cyclicals yang terdaftar di Bursa Efek Indonesia. Sedangkan sampel yang diambil dalam penelitian ini sebanyak 43 perusahaan dengan menggunakan metode purposive sampling. Data sekunder diperoleh dari BEI. Variabel independen yang digunakan adalah Current Ratio, Debt To Equity Ratio, Return On Assets, dan Total Assets Turnover. Sedangkan variabel dependen yang digunakan adalah Pertumbuhan Laba . Teknik analisis data yang digunakan adalah Analisis Linear Berganda dengan menggunakan Program Smart PLS. Hasil penelitian ini menunjukkan bahwa variabel Current Ratio, Debt to Equity Ratio, Return On Assets berpengaruh positif dan tidak signifikan terhadap variabel pertumbuhan laba. Sedangkan Total Assets Turnover berpengaruh negatif dan tidak signifikan terhadap variabel pertumbuhan laba. Kata Kunci : Consumer Non Cyclicals; Current Ratio; Debt To Equity Ratio; Return On Assets; Total Assets Turnover; Pertumbuhan Laba.